KARAKTERISASI PEMBELAJARAN LITERASI DASAR SISWA KELAS AWAL SESUAI DENGAN LEVEL KEMAMPUAN - Sri Rahmawati; Mulyadi Mulyadi; Syarifudin Syarifudin (Universitas Batanghari, 2026)
This study aims to describe the characteristics of basic literacy learning for early grade students based on ability level, also known as TaRL (Teaching at the Right Level). The subjects were 15 third-grade students at Rompo Elementary School. The test instruments consisted of an initial diagnostic test and a progress test during the learning process. The results showed that the first-level group's characteristics were introducing children to the smallest components of literacy skills: sounds and letters, and distinguishing the various phonetic variations of these letters. In Group B, students developed reading fluency through regular reading practice, building mastery of texts, and beginning to understand unusual letter combinations and pronunciations. Group C read together in small groups and answered a series of questions about the text, deduced the meaning of unfamiliar words, and moved from simple to complex concepts. Students were encouraged to practice writing daily, reading, and evaluating each other's work to strengthen their ability to spot common spelling, grammar, and punctuation errors